Overweight/obesity: Prevalence and association with maternal and fetal variables in pregnant women with pre-eclampsia - dos Santos Xavier Braga, Ana Paula; Matos Silva, Diana; de Farias Lelis, Deborah; de Oliveira Faria Baldo, Thaís; Fernandes Paraíso, Alanna; Silvana de Oliveira e Silva, Carla; Oliveira Andrade, João Marcus (Revista Unimontes Científica, 2025)
Objective: To evaluate the overweight and obesity prevalence in pregnant women with preeclampsia, as well as to test for associations between the maternal anthropometric profile, clinical, and laboratory variables, and fetal outcomes. Methods: an analytical cross- sectional study, with 178 pregnant women and their newborns attended at a reference public maternity hospital in the North of Minas Gerais. Information was collected in medical records and interviews. Odds ratio analysis was performed between the studied variables with confidence intervals of 95%, and significance level set as p <0.05. Results: the overweight/obesity prevalence in the present study was 73.03%. Regarding the maternal conditions, a statistically significant association was observed for the personal history of pre-eclampsia, parity, and platelets, and regarding the birth conditions, a statistically significant association for the cephalic perimeter <33cm was observed. Conclusion: the studied group evidenced a prevalence of overweight/obesity higher than 70% and maternal and fetal risk factors for pre-eclampsia, such as positive personal history of pre-eclampsia, number of pregnancies higher than 1, platelets count over 150.000 units/ mm 3 , and fetus cephalic perimeter lower than 33cm. Keywords: Pregnancy, obesity, pre-eclampsia, pregnancy complications, newborn.